IKLIM ORGANISASI DAN SIFAT PEKERJAAN SEBAGAI PENYEBAB TERJADINYA PELECEHAN SEKSUAL DAN PENGARUHNYA TERHADAP MOTIVASI, STRES KERJA, KEPUASAN KERJA, SERTA KINERJA KARYAWAN - Rizki Ahidika Pranantya (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2016)
This study examined the organization climate and job nature as the cause of sexual harassment and the effects toward job motivation, job stress, job satisfaction, and job performance. One hundred and twelve sales promotion girl who still carry status as college students are participating in this research. There are some findings in this research. The organization climate has a connection with job nature. Meanwhile, the organization climate and job nature affect toward sexual harrasment. The next finding is that sexual harassment has affects toward job stress, but this research is resulting a surprising finding where sexual harassment has no affects on job motivatiion and job satisfaction. Next finding is that job stress affects job motivation positively. Meanwhile, job motivation does not affect job performance. The last finding is that job satisfaction does not affect job performance. Keywords: organization climate, job nature, sexual harassment, job motivation, job stress, job satisfaction, job performance